Update in clinical and mouse microbiota research in allogeneic haematopoietic cell transplantation. Issue 6 (November 2020) - Lindner, Sarah; Peled, Jonathan U.
Abstract : Purpose of review: The intestinal microbiota plays a critical role in intestinal homeostasis and immune regulation and has been recognized as a predictor of clinical outcome in patients undergoing allogeneic haematopoietic cell transplantation (allo-HCT) and specifically a determinant of the severity of graft-versus-host disease (GVHD) in mouse models. As GVHD is the most important cause of nonrelapse mortality (NRM) after allo-HCT, understanding the mechanisms by which modifying the microbiota may prevent or decrease the severity of GVHD would represent an important advance. Recent findings: Microbiota injury was observed globally and higher diversity at peri-engraftment was associated with lower mortality. Lactose is a dietary factor that promotes post-allo-HCT Enterococcus expansion, which is itself associated with mortality from GVHD in patients and exacerbates GVHD in mice. Bacterial and fungal bloodstream infections are preceded by intestinal colonization with a corresponding organism, supporting the gut as a source for many bloodstream infections. Metabolomic profiling studies showed that GVHD is associated with changes in faecal and plasma microbiota-derived molecules. Summary: In this review, we highlight some of the most recent and important findings in clinical and mouse microbiota research, as it relates to allo-HCT. Many of these are already being translated into clinical trials that have the potential to change future practice in the care of patients.